2019
DOI: 10.3856/vol47-issue2-fulltext-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different phosphorus concentrations on growth and biochemical composition of Chaetoceros muelleri

Abstract: Chaetoceros muelleri is one of the most widely used microalgae species in aquaculture in northwestern Mexico as food for fish and crustaceans. Its importance is due to its fast growth, nutritional quality and lipid accumulation under nutrient-limiting conditions. However, the biochemical and molecular mechanisms of uptake of phosphorus (P) limiting conditions for this species is still unknown. This study aimed to analyze the growth and biochemical composition of C muelleri in response to different phosphorus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
5
10
0
Order By: Relevance
“…In the haptophyte Isochrysis galbana, chlorophyll content decreased; however, an increase in carotenoids was observed, suggesting that this may be a protection mechanism against photo-oxidative stress [102]. Recent studies in C. muelleri cultured in F media reported that the highest content of chlorophyll a was found at 72 µM Pi, while at 7 and 18 µM Pi (considered as low P concentrations in the study), the chlorophyll a content was significantly reduced [35].…”
Section: Effect Of P Limitation On the Photosynthetic Apparatus And Pigment Content In Diatomsmentioning
confidence: 61%
See 1 more Smart Citation
“…In the haptophyte Isochrysis galbana, chlorophyll content decreased; however, an increase in carotenoids was observed, suggesting that this may be a protection mechanism against photo-oxidative stress [102]. Recent studies in C. muelleri cultured in F media reported that the highest content of chlorophyll a was found at 72 µM Pi, while at 7 and 18 µM Pi (considered as low P concentrations in the study), the chlorophyll a content was significantly reduced [35].…”
Section: Effect Of P Limitation On the Photosynthetic Apparatus And Pigment Content In Diatomsmentioning
confidence: 61%
“…On the other hand, in studies carried out in Chaetoceros muelleri grown in F medium, P concentration was doubled compared to the control, and a higher content of dry biomass was found in the control treatment compared to the P excess treatment. However, no significant differences were found in cell density between the control and excess concentrations [35].…”
Section: P Effect On Growth and Biomass Productionmentioning
confidence: 66%
“…A study on S. marinoi (Bertozzini et al 2013) showed that the reduction in nitrate concentration remarkably induced a decrease in biomass production. Likewise, in Chaetoceros muelleri, growth rates and cell densities increased as the phosphate (P) concentration increased from 7 lM to 144 lM (Lovio-Fragoso et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in Chaetoceros muelleri , growth rates and cell densities increased as the phosphate (P) concentration increased from 7 μM to 144 μM (Lovio‐Fragoso et al. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of phycobiliproteins requires sufficient phosphorus because it is degraded under phosphorus starvation conditions [96]. Protein accumulation was not significantly affected under different phosphorus concentrations in Chaetoceros muelleri [97], which may be because phosphorus is not a main component of proteins. On the other hand, similar to nitrogen starvation, phosphorus limitation has been widely used to produce various high-value secondary metabolites and storage lipids and carbohydrates.…”
Section: Phosphorusmentioning
confidence: 91%